Molecular Dynamics Simulation of Imidazole Aqueous Solution at 298.15, 303.15 and 308.15 K - Y. I. Mohammed (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
M D simulation of Imidazole aqueous solution at 298.15, 303.15 and 308.15 K was carried out by using OPLS force field from this simulation we calculate RDF of N-H… OH2 and N…HOH type of interactions, the results show that the hydration shell around N-H site at 5A0 decade with the increase of temperature and reformed at 10A0, so N site has two conserved hydration shells at approximate 4 and 6A0 respectively these are stable in this temperature range but the order and number of water molecules are varying with temperature specially the hydration shell at 4A0